The Effect Cooperative Model Type Of SFE Toward Students Social Skills Viewed From The Thinking Styles Characteristics - Fauzi, Mohamad Nur (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2017)
In the process of learning to occur an interaction between teachers with students or students with other students. Interactions is a good one of the factors that support a learning success. Interactions in this study is the social skills of students. Social skills in question is how students collaborate, deliver opinions, establishing relationships with others, have a sense of empathy, and dare to take decisions. In addition, in the learning process of the students also did a thought process. Thought processes referred to in this study are thinking styles characteristic: concrete sequential (SK), abstract sequential (SA), concrete random (AK), and abstract random (AR). These studies are particularly suited to exploratory Research design to give you an idea of the situation and condition of the students processed. The purpose of this research is to study how the social skills of students viewed from the characteristics of their different thinking styles. The result is students with the characteristics of thinking styles AK has better social skills than other thinking style characteristics. In the process of learning to occur an interaction between teachers with students or students with other students. Interactions is a good one of the factors that support a learning success. Interactions in this study is the social skills of students. Social skills in question is how students collaborate, deliver opinions, establishing relationships with others, have a sense of empathy, and dare to take decisions. In addition, in the learning process of the students also did a thought process. Result this research are 1) The learning model SFE have better social skills rather than direct learning, 2) On each style of thinking gives the same influence toward social skills.